Psychologic-Pedagogical Preparation of the Future Teachers of Economy to Education Management in Non-Pedagogical University - Nataliia Aleksandrova (Pedagogical Discourse, 2014)
The author of the article analyzes the content, main goals and approaches of pedagogical and psychological preparation of future faculty at the economic university. The preparation for classroom management of future faculty is introduced. The expertise of Kyiv National Economic University is mainly focused on: its managerial, organizational and creative approaches are viewed as crucial ones. It is proved that after covering the main issues of this preparation the future faculty will be able to organize and conduct the learning process in the most efficient and fruitful way. However the author draws attention to the importance of including issues of governance culture in the pedagogical preparation. Thus she introduces a specially designed course «Lecture’s governance culture» in order to enhance students’ professional preparation.